Intelligent and real time data acquisition and evaluation to determine critical events in Intensive medicine - Portela, Filipe (2012)
Using the information regarding critical events to support decision making in Intensive Care Units would be useful. However it is seldom used in real settings as the information regarding those critical events is difficult to gather and make available in real time. The most usual procedures record only those events that are related to errors. This paper presents a solution to obtain critical events from clinical data. From data collected using an automatic and real-time data acquisition system it is possible to calculate the critical events regarding five variables that are usually monitored in an ICU. These results are presented to the medical and nursing staff in a friendly and intuitive mode. Using a color code our system provides visual warnings related to the evolution of the monitored variables values. Actually, a quick glance allows doctors to get a high level overview of the patient's condition